(untitled) (Research, Society and Development, 2021)
The aim of this study is report an experience with high school scientific initiation students, in Fortaleza-CE, about environmental sustainability during a pandemic by COVID-19. The first stage was based on thematic workshops on theoretical and practical learning with high school students from the school mentioned, in addition, there was the development of didactic material. The themes covered by the workshops were: “Environmental sustainability: what is my role in society”; “Citizenship and society in the context of the School and University”; “Management and management of solid waste in health services”; “Management of radiological waste in dental services”. The second phase consisted of conducting a situational analysis on knowledge and attitudes about the theme of environmental sustainability with students from the first to the third year of the school as public, the “Google Forms” Platform was used as a tool. The situational analysis on the perception of high school students about environmental sustainability allowed us to observe that the students pointed out important reflexes caused by the pandemic resulting from the new coronavirus.